230k views
4 votes
X^3-y^3
Factor completely, then place the answer in the proper location on the grid.

User Cowirrie
by
4.7k points

1 Answer

1 vote

For this case we must factor the following expression:


x ^ 3-y ^ 3

We have that since both terms are perfect cubes, we factor using the cube difference formula.


a ^ 3-b ^ 3 = (a-b) (a ^ 2 + ab + b ^ 2)

Where:


a = x\\b = y

So, we have to:


x ^ 3-y ^ 3 = (x-y) (x ^ 2 + xy + y ^ 2)

Answer:


x ^ 3-y ^ 3 = (x-y) (x ^ 2 + xy + y ^ 2)

User Ben Challenor
by
5.0k points